2010
DOI: 10.1111/j.1365-2834.2010.01061.x
|View full text |Cite
|
Sign up to set email alerts
|

A literature review of conflict communication causes, costs, benefits and interventions in nursing

Abstract: Nurse managers can support themselves and others in working through conflict by normalizing conflict, employing proven proactive and reactive interventions and by helping to build integrated conflict management systems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
75
0
4

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 107 publications
(80 citation statements)
references
References 93 publications
1
75
0
4
Order By: Relevance
“…However, in a review it was found that nursing students, or recent nursing graduates, often lacked knowledge in the following areas: communication, leadership, organisation, critical thinking, specific situations, and stress management. [2] These competences are in line with questions used in our study. One possible explanation for why nursing students and registered nurses rated their competence in management of conflict in a similar way could be that nursing students have theoretical competence in managing conflict and believe that this will stand them in good stead for the future.…”
Section: Discussionsupporting
confidence: 53%
See 2 more Smart Citations
“…However, in a review it was found that nursing students, or recent nursing graduates, often lacked knowledge in the following areas: communication, leadership, organisation, critical thinking, specific situations, and stress management. [2] These competences are in line with questions used in our study. One possible explanation for why nursing students and registered nurses rated their competence in management of conflict in a similar way could be that nursing students have theoretical competence in managing conflict and believe that this will stand them in good stead for the future.…”
Section: Discussionsupporting
confidence: 53%
“…[3] Research within this area has often focused on the concept of conflict management style. [2,7,8] Conflict management styles are complex, and we may use one style more than others. However, the style we use depends on the situation and the participants involved in a particular conflict.…”
Section: Cmc and Nursingmentioning
confidence: 99%
See 1 more Smart Citation
“…Work environments which offer members a sense of acceptance and connectedness positively impact patient care and nurse retention rates [43][44][45] . Building communities which emphasize these elements can help promote a cooperative orientation which encourages constructive conflict management when issues do arise.…”
Section: Collegialitymentioning
confidence: 99%
“…Quality care and patient safety are threatened when health care providers are burdened by stressful ethical conflicts that erode interpersonal trust, compromise working relationships, and fragment care. 1,24,[39][40][41][42][43][44][45] Furthermore, these compromised relationships increase patients' mortality and morbidity 44,46,47 and organizational costs. 41,48 Ethical conflicts can also delay treatment decisions 4 and increase the risk for family conflict.…”
Section: Study Procedures and Data Collectionmentioning
confidence: 99%